IMPACT OF FLOODING ON HUMAN SECURITY IN NORTHERN NIGERIA - DUBE PHILEMON ABRAK; ADELAKUN RASHEED ADEYINKA; ISHAKU AISHA YUSUF; UBON UDOH HUMAPWA; MUKHTAR BELLO MUHAMMAD; CHUKWUEDO N. HENRY; OGBUKE KINGSLEY NNAMDI (International Studies Journal)
The study provides insights into how flooding exacerbates health issues and the direct and indirect effects on physical and food security in northern Nigeria through the increased prevalence of waterborne diseases such as cholera and malaria, displacement of people, leading to overcrowded and unsanitary living conditions in temporary shelters and the disruption of agricultural activities, resulting in food shortages and increased prices, undermining food security in the region. Relying on secondary sources of data collection and utilising content analysis, the study investigates the impact of flooding on health, physical and food security in Northern Nigeria, Using the Human Security Theory (HST)   developed by Mahbub ul Haq and Amartya Sen in 1994 to emphasise the protection of individuals and communities from various threats, including environmental disasters like flooding. Findings revealed that flooding causes outbreaks of infectious diseases, inadequate sanitation, and making people vulnerable to infection, affecting mental, social, and physical health. It also causes internal displacement, homelessness, economic hardship, psychological violence, and flooding affects agricultural productivity, destroying crops and farmland, which threatens food security. This study recommended that the Nigerian government overhaul emergency response services to ensure hygienic conditions, that people have access to clean water and sanitation, and that infectious diseases are prevented after flooding. Immediate assistance should be provided to displaced persons, including food, shelter, and healthcare, as well as to relocate affected communities to construct and maintain effective drainage systems to prevent flooding and engage local communities in flood risk management and adaptation measures. Land use planning and enforcement should be improved to mitigate flood risks. It should establish reliable early warning systems to alert communities of potential floods, promote water conservation and efficient irrigation practices, and encourage crop cultivation on soils with high water-holding capacity.